Engineering Characterisation Of Epoxidized Natural Rubber-Modified Hot-Mix Asphalt - Ramez A. Al-Mansob; Amiruddin Ismail; Nur Izzi Md. Yusoff; Riza Atiq O. K. Rahmat; Muhamad Nazri Borhan; Shaban Ismael Albrka; Che Husna Azhari; Mohamed Rehan Karim (Public Library of Science, 2024)
Indexed by SCOPUS